Perancangan Mata Pisau pada Traktor Pemanen Jagung Menggunakan Solidwork - Harahap, Doa; Waskito, Waskito (Darul Yasin Al Sys, 2023)
Corn is one of the plants in agriculture that is needed in the lives of people in West Sumatra. Based on data in 2020 the need for corn is in the range of 1.2 million tons. But what can be produced is 939,466 tons. Traditional corn harvesting technology is a problem that causes corn production is not maximized. Corn harvesting tractor is one of the innovations in agricultural technology. The most important unit of the harvesting machine is the blade. The success of the machine in the harvesting process is determined by the shape and strength of the blade. Experimental testing is expensive and time consuming. Therefore, this study examines the design and simulation of blade strength on corn harvesting tractors with Solidwork software. The simulation carried out is a static analytic structural simulation. The simulation results include von-mises stress, displacement and factor of safety. Stress on the crossbar design has a maximum value of 2.168e+07 N/m^2 at the shaft connection and the inside of the bearing, maximum displacement on the side of the blade tip with a value of 1.953e-01 mm and FoS with a value of 5.553e+04. In design S the maximum stress is 2.476e+07 N/m^2, the displacement on the side of the blade tip is 2.199e-01 mm and the FoS is 1.052e+04. Both designs were given the same material AISI 1045, a force load of 87.05 N and a torque load of 41.5 Nm. The design that is suitable for use is the S shape design based on the results of the simulation and the shape that is more suitable for the harvesting process.